MARKERS OF INFLAMMATION IN DIFFERENT FORMS OF CHRONIC ABACTERIAL PROSTATITIS - E. A. Chernogubova (Вестник урологии, 2018)
Introduction. Chronic prostatitis is the most common and difficult to diagnose androurologic disease. However, the etiology, pathogenesis and pathophysiology of chronic abacterial prostatitis are not well understood.Objective. Analysis of the role of the body’s proteolytic systems in inflammatory processes in the prostate, detection of markers of inflammation in the blood, prostate secretion in various forms of chronic abacterial prostatitis / chronic pelvic pain syndrome (CAP/CPPS).Materials and methods. The study included 52 patients with inflammatory (CAP/CPPS IIIA) and 46 patients with non - inflammatory (CAP/CPPS IIIB) forms of chronic abacterial prostatitis. We determined the activity of kallikrein, level of prekallikrein, inhibitory activity α1-proteinase inhibitor and α2- macroglobulin, total arginine-esterase activity, activity of leukocyte elastase and elastase-like activity in the blood serum and the prostate secret.Results. Disturbance of metabolic processes of inflammation development in chronic abacterial prostatitis occurs against the background of imbalance of the proteinase inhibitors system, uncontrolled enhancement of proteolytic processes in the prostate in conditions of weakening of natural resistance of the organism is the most significant factor in the development of CAP/CPPS.Conclusions. The analysis of the activity of proteolytic processes in the blood and prostate secretion can serve as an additional diagnostic criterion for chronic abacterial prostatitis/chronic pelvic pain syndrome.Disclosure: TInformation about sponsorship. The publication was prepared within the framework of the implementation of the State Task of the SSC RAS for 2018. The state registration of the project № 01201363192. The author declares no conflict of interest.